The accuracy and reliability of digital measurements of gingival recession versus conventional methods - Hytham N. Fageeh; Abdullah A. Meshni; Hassan A. Jamal; Reghunathan S. Preethanath; Esam Halboub (BMC, 2019)
Abstract Background An apical shift in the position of the gingiva beyond the cemento-enamel junction leads to gingival recession. This study aimed to evaluate the reproducibility of digital measurements of gingival recession when compared to conventional measurements taken clinically using periodontal probes. Methods Gingival recession was measured at 97 sites in the oral cavity by four examiners using the following methods: CP, direct measurement of gingival recession using William's periodontal probe intraorally; CC, measurements on cast models using a caliper; DP, digital measurement on virtual models obtained by intraoral scanning, and DC, digital measurements on virtual models of dental casts. Intra-class and inter-rater correlations were analyzed. Bland Altman plots were drawn to visually determine the magnitude of differences in any given pair-wise measurements. Results In this study, good inter-methods reliability was observed for almost all the examiners ranging from 0.907 to 0.918, except for one examiner (0.837). The greatest disagreements between the raters were observed for methods; CP (0.631) followed by CC (0.85), while the best agreements were observed for methods DP (0.9) followed by DC (0.872). Conclusion Variations in measurements between examiners can be reduced by using digital technologies when compared to conventional methods. Improved reproducibility of measurements obtained via intraoral scanning will increase the validity and reliability of future studies that compare different treatment modalities for root coverage.